Implementasi Pendidikan Karakter dalam Pembentukan Kepribadian Siswa SMK Muhammadiyah Bulukumba - Muh. Nasrun (Jurnal Pendidikan dan Pembelajaran, 2024)
Abstrak This research is descriptive in nature, namely by taking data such as learning outcome value data integrated with character and personality education of students at Muhammadiyah Bulukumba Vocational School. The population in this study were 20 students of Class XI, Computer Engineering and Networking Department, Muhammadiyah Bulukumba Vocational School. To determine the sample size in this study, the sampling technique used is a non-probability technique, namely the saturated or census sampling technique. The sample size in this study is the same as the population size, namely 20 students. The data collection techniques used are observation, interview, documentation dan evaluation techniques. The data analysis techniques used are Korelasi Produkc Moment. Based on the results of the study with a significance level of 5% and N = 20, it turns out that the Ho rejection limit in the r table is 0.333. The calculated r value = 1.089 turns out to be > from r table = 0.333 meaning that the calculated r xy value is significant, so that Ho is rejected and H1 is accepted, meaning that there is a relationship between character education and the formation of the personality of students at Muhammadiyah Bulukumba Vocational School.